FACTORS FOR THE SUCCESSFUL USE OF FLUID BATHS TO ELIMINATE COMPLICATIONS DURING DEEP WELL DRILLING - Charkovskyi, V. M.; Beizyk, O. S.; Kolisnyk, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The article presents data from a comprehensive expert analysis of problems encountered during well drilling in the Carpathian oil and gas region between the 1960s and 2000s. It is noted that, despite the use of drilling fluids with a high inhibiting effect on unstable rocks, conditions may also arise that require the additional use of fluid baths to strengthen these rocks. A review of scientific works devoted to the problem of increasing the effectiveness of the use of liquid baths, both for the elimination of sticking and for the strengthening of unstable rocks, has been carried out. It was noted that most scientific works are devoted to the problem of perfecting the chemical formulations of liquid baths, while some organizational and technical-technological problems have been overlooked by researchers. As a result, the article describes a complete set of works on the installation of liquid baths, from planning to implementation at the drilling site. At the same time, organizational, technical and technological factors and the factor of perfection of the chemical formula of the bath under certain conditions of its application are analyzed. Some directions for improving the effectiveness of eliminating geological complications with the help of fluid baths are proposed, in particular, the direction related to maintaining the stability of the bath in the well during its exposure time. It is indicated at which stages of work on the installation of a fluid bath additional employees of the drilling organization are involved, what their role is in the successful performance of production operations to eliminate complications, and how they form a temporary working group from the point of view of a project approach. An equation is proposed that determines the basic conditions for the use of fluid baths in a well from the point of view of economic feasibility. To develop new chemical formulations for fluid baths, both for eliminating sticking and for strengthening unstable rocks, it is proposed to use the classification of reagents according to O.V. Aniskovtsev.